Fluid mechanics - Liggett, James A.
This text on intermediate fluids is aimed at the civil, agricultural and oceanography markets. It gives a grounding in fluid mechanics, including systematic and parallel development of the equations of fluid mechanics in integral and differential form. There is also extensive coverage of free surface flow. The book's applications are directed at shallow-water hydraulics, oceanography and wave mechanics, circulation in large bodies of water and transport. Examples, problems and historical notes are also included